Pengaruh Intensitas Penggunaan Media Sosial Terhadap Tingkat Nomophobia pada Remaja SMA di Kota Bogor - Adrian Adrian; Oktavia Oktavia (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Teknologi Nusantara, 2025)
The massive development of social media among teenagers has serious implications for mental health, one of which is the phenomenon of nomophobia, or excessive anxiety when unable to access a cell phone. This study aims to examine the effect of social media usage intensity on the level of nomophobia among high school students in Bogor City. The research design uses a quantitative approach with a cross-sectional survey method. Data were collected through an online questionnaire. When the data were not normally distributed, analysis was performed using non-parametric regression testing with the bootstrapping technique. The results showed that the intensity of social media use had a significant effect on the level of nomophobia (p < 0.001; 95% CI BCa did not include zero). These findings reinforce the Uses and Gratifications 2.0 theory and contribute to the development of digital literacy and preventive interventions in educational settings. In conclusion, the higher the intensity of social media use, the greater the tendency for adolescents to experience nomophobia. Further research is recommended using a longitudinal design and considering moderator variables such as self-control or social support to deepen understanding